Equilibrium Solubility of Carbon Dioxide in Aqueous 2-Amino-2-Methyl-1-Propanol (AMP) Blended with 2-Methylpiperidine (2MPD) at High Pressure / Siti Nabihah Jamaludin...[et al.] - Jamaludin, Siti Nabihah; Mohd Salleh, Ruzitah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
In this study, a new experimental data on CO2 absorption capacity in aqueous mixtures of 2-Amino-2-Methyl-1-Propanol (AMP) and 2-Methylpiperidine (2MPD) was measured at temperature conditions of 313.15K, 323.15K and 343.15K and pressure ranges of 400psi up to 700psi. The experiments were carried out with 0-10wt% of 2MPD and 20-30wt% of AMP. It was found that the CO2 loading capacity increased with increasing CO2 partial pressure and with decreasing temperature. The results indicated that addition of 2MPD to the aqueous AMP solution greatly enhanced the CO2 loading capacity by 0.93% up to 45.41%. Simple correlations of solubility as a function of temperature and CO2 partial pressure suggested by Jou and Mather Model was used to predict the solubility of CO2 in the mixtures and found to be in a good agreement with the experimental value.